HIV infection and exposure is associated with increased cariogenic taxa, reduced taxonomic turnover, and homogenized spatial differentiation for the supragingival microbiome - Allison E. Mann; Ciara Aumend; Suzanne Crull; Lauren M. O’Connell; Esosa Osagie; Paul Akhigbe; Ozoemene Obuekwe; Augustine Omoigberale; Matthew Rowe; Thomas Blouin; Ashlyn Soule; Colton Kelly; et al. (Microbiome)
Abstract Background The oral microbiome consists of distinct microbial communities that colonize various ecological niches within the oral cavity, the composition of which are influenced by nutrient and substrate availability, host genetics, diet, behavior, age, and other diverse host and environmental factors. Unlike other densely populated human-associated microbial ecosystems (e.g., gut, urogenital), the oral microbiome is directly and frequently exposed to external influences, contributing to its relatively lower stability over time. In individuals with compromised immunity, such as those living with HIV, the composition and stability of the oral microbiome may be especially vulnerable to disruption. Cross-sectional studies of the oral microbiome in children living with HIV capture a glimpse of this temporal dynamism, yet a full appreciation of the relative stability, robusticity, and spatial structure of the oral environment is necessary to understand the role of microbial communities in promoting health or disease in the context of HIV. Here, we investigate the spatial and temporal stability of the oral microbiome over three sampling time points in the context of HIV infection and exposure. Individual teeth were sampled from a cohort of 565 Nigerian children with varying levels of tooth decay severity (i.e., caries disease). We collected 1960 supragingival plaque samples and characterized the oral microbiome using a metataxonomic approach targeting an approximately 478 bp region of the bacterial rpoC gene. Results Both HIV infection and exposure have significant, if subtle, effects on the stability of the supragingival plaque microbiome. Specifically, we observed (1) a slight but significant reduction in taxonomic turnover among HIV-exposed and infected children; (2) an association between HIV infection and a more homogenized oral community across the anterior and posterior dentition in children living with HIV; and (3) a relationship between impaired immunity, lower taxonomic turnover over time, and an elevated frequency of cariogenic taxa, including Streptococcus mutans, in children living with HIV. Conclusions Despite the influence of various contributing factors, we observe an effect of HIV status on both the temporal and spatial stability of the oral microbiome. Specifically, the results presented here indicate that the oral microbiome shows less community change over time in children living with or exposed to HIV, which we hypothesize may be linked to a reduced capacity to adapt to environmental changes. The observed taxonomic rigidity among children living with HIV may signal community dysfunction, potentially leading to a higher incidence of oral diseases, including caries, in this cohort. Video Abstract